Annual survey of English law. - London School of Economics and Political Science. Dept. of Law. (London The London school of economics and political science (University of London) Dept. of Law.)
Each subdivision includes sections "Legislation", "Case law" and "Literature".
Keywords: Law -- Great Britain; Law reports, digests, etc. -- Great Britain